tinyDSM: data-oriented middleware for low-power IoT devices = tinyDSM: zorientowana na dane warstwa pośrednia dla energooszczednych urządzeń Internetu rzeczy - Zielony, Przemysław; Michta, Emil; Piotrowski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
Developing applications for distributed measurement and control systems based on wireless sensor networks or, general, on the Internet of Things (IoT) devices requires knowledge and experience. This task can be simplified by approaching it in a modular way.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne